Maqashid Sharia Implementation in Indonesia and Bahrain - Erik Nugraha; Lucky Nugroho; Citra Lindra; Wiwin Sukiati (Faculty of Economic and Business, 2020)
This study aims to analyze the performance of Islamic banking in Indonesia and Bahrain from the perspective of the maqashid shariah index. Performance is the success of an organization in implementing its strategy so that its achievement on the targets set. Maqashid shariah is a measurement of Islamic banking performance following the objectives and characteristics of Islamic banking. The research method used is descriptive and comparative methods, while the data analysis technique used is the independent t-test. The results of this study are that there is no significant difference between the application of Islamic maqashid in Indonesia and the implementation of Islamic maqashid in Bahrain. Thus, the application of Islamic values and the application of sharia maqashid has been integrated with Islamic bank business activities so that different government policies or regulations because each country has a specific constitution, then the impact is not significant or does not affect the implementation of sharia maqashid on operational and business activities in Islamic banks.JEL Classification: M41, M48, Z12 How to Cite:Nugraha, E., Nugroho, L., Lindra, C. N., & Sukiati, W. (2020). Maqashid Sharia Implementation in Indonesia and Bahrain. Etikonomi: Jurnal Ekonomi, 19(1), 155 – 168. https://doi.org/10.15408/etk.v19i1.14655.